A short neuropsychological evaluation of patients with primary Sjögren's syndrome - Dóra-Neide Rodrigues; João Sergio Ignácio Hora; Maria Cecília Fonseca Salgado; Renata Alves Paes; Claudia Cristina Ferreira Vasconcelos; J. Landeira-Fernandez; Regina Maria Papais Alvarenga (Arquivos de Neuro-Psiquiatria)
Objective: To investigate cognitive deficits in patients with primary Sjögren’s syndrome (PSS). Method: Eighteen patients with PSS, aged between 25 and 61 years, were subjected to a short neuropsychological battery and compared with 18 patients with multiple sclerosis and 18 healthy controls. Results: The analysis of variance (ANOVA) revealed that the clinical groups had significantly worse performance than the control group on the Rey Auditory Verbal Learning Test 3; (F 2,53 =3.500, p=0.038) and 7 (F 2,53 =5.068, p=0.010). The clinical groups had elevated levels of depression on the Beck Depression Inventory (BDI); (p=0.003). The analysis of the data from the Trail Making Test B-A revealed a significant difference between the clinical and control groups (p=0.023). The analysis of covariance with BDI score as a covariate, did not change the outcome. Conclusion: Our study revealed cognitive deficits in patients with PSS detectable by a short neuropsychological battery.